Upaya Pengenalan Mitigasi Bencana Sejak Dini Melalui Sosialisasi Mitigasi Bencana di SDN Se-Desa Sambirejo - Indah Respati Kusuma Sari; Nashrum Minallah (Lembaga Pengembangan Kinerja Dosen, 2024)
Indonesia has very diverse geographical conditions and regional landscapes, this causes Indonesia to have a very high risk of vulnerability to natural disasters. According to the international body that handles disaster risk, namely the United Nations Office for Disaster Risk Reduction (UNISDR), Indonesia is an area with very high disaster risk. Regarding the occurrence of natural disasters, of course there is a need for a disaster management system that goes through several stages and is carried out with the aim of reducing the risk of disasters occurring.